Diastereoselectivity in Diels–Alder Cycloadditions of Erythrose Benzylidene-acetal 1,3-Butadienes with Maleimides - Salgueiro, Daniela A. L.; Duarte, Vera C. M.; Sousa, Cristina E. A.; Alves, Maria J.; Gil Fortes, António (Synlett, 2012)
Maleimides were combined with d-erythrose benzylidene-acetal 1,3-butadienes to study the facial selectivity of the Diels–Alder cycloadditions. The selectivity was found to range from moderate to good. The reaction diastereotopicity can be reversed with the temperature. Simultaneous coordination of the diene, having a free hydroxy group, and maleimide to a chiral bimetallic Lewis acid catalyst (LACASA–DA reaction) occurs with complete diastereocontrol to give a single adduct, using an extra chiral inductor either (R)- or (S)-BINOL.
Keywords: maleimides; d-erythrose benzylidene-acetal 1,3-butadiene; Diels–Alder cycloaddition; selectivity